2009
DOI: 10.1111/j.1526-4610.2009.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild Head Trauma and Chronic Headaches in Returning US Soldiers

Abstract: Objective.-To determine the incidence and types of head or neck trauma and headache characteristics among US Army soldiers evaluated for chronic headaches at a military neurology clinic following a combat tour in Iraq.Background.-Head or neck trauma and headaches are common in US soldiers deployed to Iraq. The temporal association between mild head trauma and headaches, as well as the clinical characteristics of headaches associated with mild head trauma, has not been systematically studied in US soldiers retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
100
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 19 publications
11
100
1
Order By: Relevance
“…Even the authors of the ICHD diagnostic criteria acknowledge the difficulty in distinguishing a high general population prevalence tensiontype headache from PTH occurring weeks or months after trauma (The International Classification of Headache Disorders, 2004). Our results are similar to those found by Theeler and Erickson (2009), who examined the temporal association of headaches following mild head or neck trauma in a military population, and found that only 27% of headaches developed within a week post-trauma. Whether such classification, or misclassification, of headache after TBI is important is under debate.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Even the authors of the ICHD diagnostic criteria acknowledge the difficulty in distinguishing a high general population prevalence tensiontype headache from PTH occurring weeks or months after trauma (The International Classification of Headache Disorders, 2004). Our results are similar to those found by Theeler and Erickson (2009), who examined the temporal association of headaches following mild head or neck trauma in a military population, and found that only 27% of headaches developed within a week post-trauma. Whether such classification, or misclassification, of headache after TBI is important is under debate.…”
Section: Discussionsupporting
confidence: 80%
“…Classification is primarily based on time of onset after injury or regaining consciousness (within 7 days), and chronicity of headache based on duration of headache lasting less than or greater than 3 months (acute versus chronic). However, several studies have reported a longer latency between injury and PTH and a higher incidence of chronic PTH than one would expect based on the ICHD definition (Martins et al, 2009;Theeler and Erickson, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In alternate specifications, we also include controls for predeployment migraine status, a neuroticism scale, and health, which should not affect our estimates of the effect of combat exposure if deployment assignment is exogenous. 9 A similar pattern of results is observed when we restrict the sample to only those who were serving in the Army. These findings are shown in Appendix Table 2. 18 firefight.…”
supporting
confidence: 63%
“…3). Migraines have been found to account for nearly 75 percent of post-traumatic headaches observed in soldiers (Theeler et al, 2008;Vargas, 2009) and have been linked to blast-or explosion-induced mild TBI (Vargas, 2009;Seifert and Evans, 2010;Theeler and Erickson, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation